Identification Arbuscular Mycorrhiza Fungi (Amf) Legume Plant On Microscopik Consevation Tillage Cropping Season To 29 - Sari, Sismita; Kumastuti, Any; Indrawati, Wiwik (Politeknik Negeri Lampung., 2017)
Arbuscular Mycorrhiza Fungi (AMF) is a form of mutualistic symbiosis between fungi and plant roots. FMA existence in soil is influenced by several agricultural activities such as tilling and fertilizing. The purpose of this study (1) Obtaining data on the number of FMA in each treatment and conservation tillage . (2) Knowing the types FMA in each treatment and conservation tillage planting season to 29. The study was a randomized block design (RAK) , arranged as factorial (2x3), with three replications. The first factor is the intensive tillage (T1), no-tillage (Zero Tillage) (T2) Minimum tillage (Minimum Tillage), and Land Intensive (Full Tillage) (T3); and the second factor is without fertilizer N (N0) and fertilizer application of 100 kg N ha-1 (N1), and Fertilizer of 200 kg N ha-1 (N2). The method used in this study is a description method by observation techniques, the method used for the isolation of spores of strain engineering castings and followed by centrifugation. Observations were made using a microscope binoculars and digital camera, the spores are observed then grouped based on their morphological characters, identification of mycorrhizal done using a guide book